Intraday variation of ankle dorsiflexion in short-track speed skaters - Claudel, J.; Turner, É.; Clément, J. (International Journal of Sports Physiology and Performance, 2024)
Purpose Optimal ankle dorsiflexion range of motion plays a vital role in attaining the essential crouched posture necessary for excelling in speed skating. The purpose of this study was to determine how the ankle dorsiflexion angle evolves throughout a day of training and to identify the factors that influence this angle.